Determinación del impacto de la formación continua en el sector sanitario: diseño de un modelo de relaciones entre dimensiones - Carballo Santaolalla, Rafael; Biencinto López, Chantal (Revista Complutense de Educación, 2006)
The objective of this article is to approach a thematic as complex as the evaluation of the impact is. To determine the impact which the training courses produce, it is of vital importance for the ones in charge of planning and of distributing the courses of continuous training, since the evaluation of the impact, like so, is the key for the decision making. The measurement of the impact of the training, usually, it is made on the basis of three criteria: first the satisfaction; secondly, the use of the training that the user does; and, thirdly, the economic repercussion of the training.